INTERAKSI PERLAKUAN MIKORIZA DAN INOKULUM Rhizobium sp TERHADAP PERTUMBUHAN DAN PEMBENTUKAN BINTIL AKAR Mucuna bracteata - Mardiana Wahyuni; Ricky Elmando Saragih; Mariani Sembiring (Politeknik Negeri Lampung., 2020)
The purpose of this study was to determine the effect of mycorrhizal treatment and inoculation of Rhizobium sp on the growth and formation of Mucuna bracteata root nodules. The study was conducted in the STIPAP Medan experimental garden. The study was conducted in April - July 2019. The study used 2 factorial randomized block design (RBD) methods consisting of 3 and 3 treatments with 4 replications, so that the total sample was 36 seedlings. Parameters observed were length of tendrils, number of leaves, number of root nodules, dry weight of root nodules, chlorophyll content, leaf N content and the degree of root infection. The data obtained were statistically analyzed by analysis of variance (ANOVA) with the test 5% significant difference. The results showed that the best single treatment of Mikoriza in this study was M2 with a dose of 40 g/seed, which affected in length of tendrils. Rhizobium sp application significantly affected the length of tendrils, number of leaves, number of nodules at the best single treatment is R2 with a dose of 0.6 ml/seed. Interaction of mycorrhizal and Rhizobium sp treatment showed a significant effect on M2R2 treatment, namely mycorrhizal application with a dose of 40 g/seed and Rhizobium sp application with a dose of 0.6 ml/seed had the best growth for several observational parameters.